2010
DOI: 10.1007/s11999-009-1100-7
|View full text |Cite
|
Sign up to set email alerts
|

Fine Needle Aspiration for Clinical Triage of Extremity Soft Tissue Masses

Abstract: Background Fine needle aspiration cytology (FNAC) is a rapid and low-morbid alternative to open biopsy or needle core biopsy for soft tissue masses. Numerous reports describe its use with metastatic or recurrent lesions, but FNAC is less accepted for primary lesions. Questions/Purposes We wished (1) to estimate the sensitivity, specificity, and positive and negative predictive values of FNAC for diagnosing malignancy; (2)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
49
1
9

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 31 publications
0
49
1
9
Order By: Relevance
“…Therefore, less invasive techniques have emerged [ Fine-needle aspiration is usually accepted for documentation of metastases and local recurrences, especially if prior samples are available for comparison [21]. In fact, although this technique distinguishes mesenchymal from metastatic tumors, malignant from benign lesions, and high from low grade sarcomas, it is unable to precisely subtype sarcomas [21]. In regard to this technique, the literature reports a wide range of sensitivities (86%-100%), specificities (36%-100%) and diagnostic accuracies (21.9%-98%).…”
Section: Soft Tissue Biopsiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, less invasive techniques have emerged [ Fine-needle aspiration is usually accepted for documentation of metastases and local recurrences, especially if prior samples are available for comparison [21]. In fact, although this technique distinguishes mesenchymal from metastatic tumors, malignant from benign lesions, and high from low grade sarcomas, it is unable to precisely subtype sarcomas [21]. In regard to this technique, the literature reports a wide range of sensitivities (86%-100%), specificities (36%-100%) and diagnostic accuracies (21.9%-98%).…”
Section: Soft Tissue Biopsiesmentioning
confidence: 99%
“…However, these studies usually exclude nondiagnostic samples, reducing the reliability of results [1]. Ng et al [21] retrospectively examined the diagnostic accuracy of 432 fine-needle aspirations performed in soft tissue masses of extremity. They reported that the nature of the lesion was indeterminate or the sample was inadequate in 8.1% of the cases.…”
Section: Soft Tissue Biopsiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnostic accuracy of FNAC of soft tissue tumors in distinguishing benign and malignant lesion is very high. 5 The level of diagnostic specificity and sensitivity are approximately 95% for establishing a definite diagnosis of sarcomas. 6 Thus, it is a useful technique for the initial diagnosis of soft tissue tumors as well as for identification of recurrent and metastatic cases.…”
mentioning
confidence: 99%
“…Die in der Regel mit kaum oder nur minimalen Komplikationen behaftete FNP stellt durchaus eine technisch wenig anspruchsvolle, ambulante Alternative dar im Vergleich zu einer offenen Biopsie mit deutlich größeren Risiken im Zusammenhang mit der Anäs-thesie, Nachblutung, Infektion oder Kontamination des Stichkanals. Kosteneffizienz und schnellere Verarbeitungszeiten gehören zu den weiteren wichtigen Vorteilen der FNP [1,13,14,[23][24][25]28].…”
unclassified